2020
DOI: 10.1093/cvr/cvaa125
|View full text |Cite
|
Sign up to set email alerts
|

Human-induced pluripotent stem cells for modelling metabolic perturbations and impaired bioenergetics underlying cardiomyopathies

Abstract: Normal cardiac contractile and relaxation functions are critically dependent on a continuous energy supply. Accordingly, metabolic perturbations and impaired mitochondrial bioenergetics with subsequent disruption of ATP production underpin a wide variety of cardiac diseases, including diabetic cardiomyopathy, dilated cardiomyopathy, hypertrophic cardiomyopathy, anthracycline cardiomyopathy, peripartum cardiomyopathy, and mitochondrial cardiomyopathies. Crucially, there are no specific treatments for preventing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 238 publications
0
9
0
Order By: Relevance
“…Cardiomyocytes differentiated from patient-specific iPSCs and the genetically edited isogenic controls have been shown to provide valuable insights into the mechanisms of inherited cardiac diseases ( Eschenhagen and Carrier, 2019 ; Ramachandra et al, 2021 ). However, disease models using 2D cultured iPSC-CMs present some clear limitations in terms of morphology, contractility, and electrophysiology, resembling human cardiomyocytes at the embryonic stage rather than adult ( Sewanan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyocytes differentiated from patient-specific iPSCs and the genetically edited isogenic controls have been shown to provide valuable insights into the mechanisms of inherited cardiac diseases ( Eschenhagen and Carrier, 2019 ; Ramachandra et al, 2021 ). However, disease models using 2D cultured iPSC-CMs present some clear limitations in terms of morphology, contractility, and electrophysiology, resembling human cardiomyocytes at the embryonic stage rather than adult ( Sewanan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we demonstrated that this method can be applied directly to the measurement of calcium signaling in individual CMs and results in increased data collection efficiency from 20 to 80% by binding a biotinylated CM to a streptavidin surface. The overarching significance of these methods extends beyond studying primary CMs to the increasingly used induced pluripotent derived CMs in mechanistic and therapeutic studies. − …”
Section: Discussionmentioning
confidence: 99%
“… 17 Hypertrophied cardiomyocytes are subjected to a metabolic switch, similar to the embryonic condition, from fatty acids to glucose. 2 , 28 , 29 Interestingly, it was suggested that this switch exists independently of the energy demand, probably correlating to biosynthetic/anabolic demands of the cell. 30 Furthermore, fructolysis, fructose metabolism, provides has been implicated in the pathology of hypertrophy.…”
Section: Cardiomyocyte Eventsmentioning
confidence: 99%